Comparison and Validation of Preoperative Planning Techniques for Distal Femoral Osteotomies and Proximal Tibial Osteotomies - Zhang, David T.; Principe, Peter S.; Fragomen, Austin T.; Rozbruch, S. Robert (The Journal of Knee Surgery, 2020)
Preoperative planning is important for accurate intraoperative execution in many surgical fields. Planning for distal femoral osteotomies (DFOs) and proximal tibial osteotomies (PTOs) consists of choosing the level of the osteotomy, measuring the angle of the osteotomy based on hip-knee-ankle alignment, and choosing a proper osteotomy wedge size. Medical imaging IT solutions company Sectra has implemented a new osteotomy tool in their radiographic system that is simpler than the accepted standard of modified center of rotation of angulation (mCORA) technique, yet unvalidated. In this study, we aim to compare the Sectra osteotomy tool versus the mCORA technique to measure the osteotomy angles as well as wedge sizes in both DFOs and PTOs to validate this new tool.We enrolled n = 30 consecutive patients with DFOs and n = 30 PTOs from the last year. The Pearson correlation coefficient (PCC) along with descriptive statistics was used to evaluate for similarity between the two techniques. We also compared interobserver and intraobserver reliability using intraclass correlation coefficients (ICC).The PCC for osteotomy angles in DFOs and PTOs were both 0.998 (p < 0.001 for both). For wedge sizes, the PCC in DFOs was 0.993 and 0.980 in PTOs (p < 0.001 for both). ICCs were high for both interobserver measurements in osteotomy angles and wedge sizes (range: 0.989–0.999) as well as intraobserver measurements (0.994–0.999).The Sectra osteotomy tool is a validated tool for preoperative measurements of DFOs and PTOs. It is reliable and simpler than the current practice of the mCORA technique. We suggest future studies to analyze this Sectra osteotomy tool in other settings as to incorporate it into widespread clinical use.
Keywords: preoperative planning; distal femoral osteotomy; proximal femoral osteotomy